Money, Inflation and Output: Understanding the cornerstones of a monetary union in East Africa Community - Scholastica Achieng Odhiambo (European Scientific Journal, ESJ, 2017)
The advent of the East Africa Monetary Union in the East Africa Community region is bound to bring about significant change in monetary policy management in terms of money growth strategies, inflation and output growth overtime. The monetary policy will depend mainly on the objective of the umbrella regional monetary authority credibility in terms of managing inflation-output trade-off as result of monetary policy. The objectives of study are measuring the determinants of inflation, measuring output-inflation trade-off, monetary policy reaction function and money demand in EAC. The study used panel data for the period 1990-2010 covering 5 countries of the EAC. Static and dynamic panel data estimation methods were employed, namely: fixed effect model, Arellano-Bond dynamic panel model and systemic dynamic panel model by Arellano-Bover Model/Blundell-Bond. The result indicate that foreign price increases inflation while growth in GDP and M2 reduces inflation. The previous year inflation also contributed to subsequent year inflation. There exist output-inflation tradeoff and expected inflation tend to affect the existing inflation in EAC. Evidently, current inflation also had a positive influence on funds rates in the monetary policy reaction function. For money demand, previous year real money balance increase money demand in the current period while, fund rates had a marginal influence. In conclusion money, inflation and output interaction are pertinent to future stability of EAMU in the region